2018
DOI: 10.3389/fpls.2018.00402
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping for Important Agronomic Traits in Safflower (Carthamus tinctorius L.) Core Collection Using Microsatellite Markers

Abstract: Carthamus tinctorius L. (safflower) is an important oilseed crop producing seed oil rich in unsaturated fatty acids. Scarcity of identified marker-trait associations is a major limitation toward development of successful marker-assisted breeding programs in safflower. In the present study, a safflower panel (CartAP) comprising 124 accessions derived from two core collections was assayed for its suitability for association mapping. Genotyping of CartAP using microsatellite markers revealed significant genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 66 publications
4
47
1
Order By: Relevance
“…This purpose is best served by a core collection which is designed to capture maximum available/possible diversity (genetic, phenotypic and geographical) of the entire population, with limited number of individuals having low or no kinship among them (Korte et al, 2012). Core collections have been used as an association panel for GWAS in different studies (El Bakkali et al, 2013;Zhang et al, 2014;Perseguini et al, 2015;Ambreen et al, 2018). In case of rice, limited attempts have been made to use a core collection as an association panel.…”
Section: Introductionmentioning
confidence: 99%
“…This purpose is best served by a core collection which is designed to capture maximum available/possible diversity (genetic, phenotypic and geographical) of the entire population, with limited number of individuals having low or no kinship among them (Korte et al, 2012). Core collections have been used as an association panel for GWAS in different studies (El Bakkali et al, 2013;Zhang et al, 2014;Perseguini et al, 2015;Ambreen et al, 2018). In case of rice, limited attempts have been made to use a core collection as an association panel.…”
Section: Introductionmentioning
confidence: 99%
“…The representation of safflower accessions from such a wide range of countries in the admixture population might be due to their use in international breeding programs. Other important factors like mutation, migration and selection by humans might also be responsible for the occurrence of admixture populations in safflower accessions of different origin [21,27].…”
Section: Genetic Structure and Diversity In Safflower Panelmentioning
confidence: 99%
“…Earlier studies reported different loci/markers linked with 100-seed weight. Ambreen et al [21] reported two loci (NGSaf_306 and NGSaf_309) associated with 100-seed weight utilizing SSR markers. Mirzahashemi et al [51] identified one QTL (qThsw5) associated with 100-seed weight.…”
Section: Marker-trait Associations For 100-seed Weightmentioning
confidence: 99%
See 2 more Smart Citations